Data Detection Algorithms for BICM Alternate-Relaying Cooperative Systems With Multiple-Antenna Destination - Marey, Mohamed; Mostafa, Hala; Dobre, Octavia A.; Ahmed, Mohamed H. (IEEE transactions on vehicular technology, 2016)
This paper proposes two new data detection algorithms for decode-and-forward alternate-relaying cooperative communication systems. These algorithms are discussed in the context of bit-interleaved coded modulation transmission with a multiple-antenna destination. The interference signal, resulting from the concurrent transmission of the source and one of the relays, is exploited as a beneficial resource to develop an optimal data detection algorithm. We show that the optimal algorithm can be implemented by parallel demappers, each based on a family of Bahl, Cocke, Jelinek, and Raviv algorithms, connected to parallel decoders in an iterative way. Due to the need to buffer the entire frame before decoding, the optimal algorithm suffers from long processing time. A suboptimal algorithm is also proposed to avoid this problem, where each packet is decoded by using two consecutive received packets. The suboptimal algorithm reduces processing time, complexity, bandwidth loss, and memory size with a slight increase in the bit error rate (BER). The BER performance of the proposed algorithms is evaluated via Monte Carlo simulations, and the results indicate their effectiveness in improving the BER performance.